1990
DOI: 10.1159/000171971
|View full text |Cite
|
Sign up to set email alerts
|

Variables Influencing the Choice and Outcome of Noncurative Surgery for Advanced Gastric Cancer

Abstract: Of 550 patients with gastric cancer presenting in an 18-year period, 274 (49.8 %) underwent noncurative surgery. Surgery was noncurative due to invasion of adjacent organs (T4) in 19.7% of patients, extensive lymph node involvement (N3) in 4%, unresectable distant metastases in 27.7% or a combination of all three conditions in 48.5% of cases. Resection was carried out in 41.4% of patients with primary situated in the antrum and in only 12.2.% with multicentric primary ( p < 0.001). Overall operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…A number of reports on the prognosis of patients with malignancies other than EGC have demonstrated that as the number of metastatic lymph nodes increases the posttreatment outcomes worsen [33][34][35][37][38][39][40][41][42]. In this study, however, the number of metastatic lymph nodes was not found to be of prognostic significance.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…A number of reports on the prognosis of patients with malignancies other than EGC have demonstrated that as the number of metastatic lymph nodes increases the posttreatment outcomes worsen [33][34][35][37][38][39][40][41][42]. In this study, however, the number of metastatic lymph nodes was not found to be of prognostic significance.…”
Section: Discussioncontrasting
confidence: 77%
“…Lymph node metastasis has been regarded as a prognostic factor for esophageal [32][33][34][35] and colorectal [36,37] cancer. Many studies focused on gastric cancer have revealed that node involvement is associated with worse outcomes when the analyses include advanced tumors [38][39][40][41][42][43][44]. Even if the depth of tumor invasion is limited to the submucosa, the presence of metastatic lymph nodes is observed to decrease survival rates in esophageal [45,46] and colorectal [47] cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Opinions are divided as to whether total gastrectomy is a suitable procedure for palliation. Our data cannot be used to resolve this controversy, and the choice of operation must be made individually (5,35,37).…”
Section: Discussionmentioning
confidence: 96%